Pelvic exenteration surgery in patients with locally advanced castration‐naïve and castration‐resistant, symptomatic prostate cancer. (16th May 2020) - Heidenreich, Axel; Bludau, Mark; Bruns, Christiane; Nestler, Tim; Porres, Daniel; Pfister, David Johannes Karl Paul
Abstract : Objectives: To evaluate retrospectively the surgical, symptomatic and oncological outcomes of pelvic exenteration surgery (PES) in men with significant intrapelvic complications of locally advanced castration‐sensitive (CSPC) and castration‐resistant prostate cancer (CRPC). Patients and Methods: A total of 103 patients with locally advanced progressive and symptomatic CSPC or CRPC underwent PES (radical cystoprostatectomy, n = 71 [68.9%]; radical prostatectomy with continent vesicostomy, n = 9 [8.7%]; total exenteration, n = 23 [22.3%]). All patients underwent local staging via magnetic resonance imaging, cystoscopy and rectoscopy. Systemic staging was carried out with chest, abdominal and pelvic computed tomography scans and bone scans. Peri‐operative complications were assessed according to Clavien–Dindo classification. Symptom‐free and overall survival were evaluated using the Kaplan–Meier method. Statistical tests were two‐tailed with a P value <0.05 taken to indicate statistical significance. Results: After a median (range) follow‐up of 36.5 (3–123) months, the symptom‐free survival rate at 1 and 3 years was 89.2% ( n = 89) and 64.1% ( n = 66), respectively. The median symptom‐free survival was 27.9 months. A total of 78.6% of the patients were symptom‐free during their remaining lifetime. The overall survival rate at 1 and 3 years was 92.2% and 43.7%, respectively, and the median overall survival was 33.6 months. Clavien–Dindo grades 2, 3 and 4 complications developed in 31 (30.6%), 12 (11.6%) and eight patients (8.1%), respectively. Conclusion: Pelvic exenteration surgery is technically feasible in well‐selected patients, resulting in symptom relief in >90% of patients, covering 80% of their remaining lifetime.